The Dual Nature of Cellular Senescence: From Aging Signature to Regenerative Catalyst - Peng Li; Yi Yang; Xiang Qin; Juan Liao (Research)
This perspective critically examines the paradigm-shifting findings regarding cellular senescence’s dual role in tissue biology, particularly focusing on its unexpected regenerative potential in hair growth. While cellular senescence has traditionally been viewed as a detrimental process associated with aging and tissue dysfunction, research has revealed its surprising beneficial effects on tissue regeneration. We analyze the groundbreaking discovery that senescent melanocytes can stimulate hair follicle stem cells through the osteopontin–CD44 signaling pathway, challenging the conventional understanding of senescence. This perspective also evaluates the implications of this finding for both basic research and therapeutic applications, suggesting that cellular senescence represents a complex, context-dependent phenomenon rather than a uniformly detrimental process. We discuss how this new perspective necessitates a more nuanced approach to senescence-targeted therapies and opens novel therapeutic possibilities for hair loss treatment. This analysis underscores the importance of understanding senescent cell heterogeneity and their diverse functions in tissue homeostasis, which could lead to more precise therapeutic strategies in regenerative medicine.